Assessment of Reporting Quality in Randomized Controlled Trials of Acupuncture for Primary Insomnia with CONSORT Statement and STRICTA Guidelines. (17th February 2022) - Yang, Jinsong; Yu, Fanjun; Lin, Keyi; Qu, Haotian; He, Yihan; Zhao, Jing; Feng, Fen; Pan, Litao; Kui, Yu
Abstract : Aim . To assess the reporting quality of randomized controlled trials (RCTs) on acupuncture for primary insomnia (PI). Methods . Seven Chinese and English databases were searched for publication reporting RCTs on acupuncture for PI from the inception of the databases to August 6, 2021. The internationally recognized Consolidated Standards of Reporting Trials (CONSORT) statement and the International Standards for Reporting Interventions in Controlled Trials of Acupuncture (STRICTA) guidelines were used to evaluate the reporting quality. The agreement between two researchers was calculated by Cohen's kappa. Results . A total of 102 eligible RCTs were assessed. According to the CONSORT statement (2017), the positive reporting rates of items such as "abstract, " "background, " "participants, " and "numbers analyzed" were above 80%. However, the positive reporting rates of items such as "sample size, " "randomization implementation, " "Outcomes and estimation, " "Ancillary analyses, " and "Registration" were below 20%. According to STRICTA guidelines, the positive reporting rates of items such as "style of acupuncture, " "reasons for acupuncture treatment, " "Number of needles inserted, " "Needle retention time, " "Treatment regimen, " and "precise description of the control intervention" were above 80%. However, the positive reporting rates of items such as "setting and context of treatment" and "practitioner background" were below 20%. Conclusion . It is essential to advocate the endorsement of the CONSORT statement and STRICTA guidelines to improve the quality of acupuncture RCT reports.